2018
DOI: 10.1107/s2053273318003224
|View full text |Cite
|
Sign up to set email alerts
|

Precise implications for real-space pair distribution function modeling of effects intrinsic to modern time-of-flight neutron diffractometers

Abstract: Total scattering and pair distribution function (PDF) methods allow for detailed study of local atomic order and disorder, including materials for which Rietveld refinements are not traditionally possible (amorphous materials, liquids, glasses and nanoparticles). With the advent of modern neutron time-of-flight (TOF) instrumentation, total scattering studies are capable of producing PDFs with ranges upwards of 100-200 Å, covering the correlation length scales of interest for many materials under study. Despite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 65 publications
(39 reference statements)
3
38
0
Order By: Relevance
“…The limited Q-space resolution in turn affects the PDF by damping the G(r) function, i.e. reducing the PDF peak intensities with increasing r (Petkov, 2012;Olds et al, 2018). This effect is accounted for by fitting the parameter Q damp to data from a calibrant.…”
Section: Instrumental Broadeningmentioning
confidence: 99%
“…The limited Q-space resolution in turn affects the PDF by damping the G(r) function, i.e. reducing the PDF peak intensities with increasing r (Petkov, 2012;Olds et al, 2018). This effect is accounted for by fitting the parameter Q damp to data from a calibrant.…”
Section: Instrumental Broadeningmentioning
confidence: 99%
“…Q-dependent resolution function. Even though most PDF beamlines operate at settings that result in a rather broad resolution function, these two parameters are not really sufficient to describe these effects, especially in cases of complex resolution functions like the ones found in neutron time-of-flight diffractometers (Olds et al, 2018). To deal with complex resolution functions, Tucker et al (2001) modified the inverse transformation method originally developed by Pusztai & McGreevy (1997).…”
Section: Figurementioning
confidence: 99%
“…This results in the lining up of all the diffraction peaks in effective TOF. Previous studies have shown that failing to align the individual spectra well manifests as an unusual peak shape in the summed spectra (Olds et al, 2018). Then the single summed spectrum is treated according to the equation scheme…”
Section: Instrument Calibration and Data Reductionmentioning
confidence: 99%
“…The quality of refinement matches or exceeds that available at other modern neutron total scattering beamlines. Factors influencing the quality of neutron TOF PDF data were recently reviewed (Olds et al, 2018). POWGEN's overall high resolution results in observable intensities exceeding 200 Å À1 in real space, while the influence of its near linear Ád/d (equivalent to ÁQ/Q) resolution behavior displayed in Fig.…”
Section: Figure 10mentioning
confidence: 99%